2021
DOI: 10.1021/acsenergylett.1c02554
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemically n-Doped CsPbBr3 Nanocrystal Thin Films

Abstract: Electrochemical doping is a promising strategy to dope halide perovskites without introducing impurities into the lattice. However, n-type doping of halide perovskites remains challenging due to intrinsically limited electrochemical stability. Herein, we report electrochemically n-doped CsPbBr3 nanocrystal (NC) films within electrochemically stable potential windows (−0.9–0.5 V vs Ag/AgNO3). Compared to bulk films with limited accessible surface area for cation charge compensation, NC films show more efficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…[5,6] Despite the challenge introduced by mobile ions, many strategies have been applied in an attempt to dope perovskites including substitution of lattice ions, [7][8][9][10][11][12][13][14][15] chemical reactions with vapors, [16][17][18] treatment with molecular oxidizers and reducers, [19][20][21][22][23][24] and electrochemical techniques. [25][26][27][28] However, to the best of our knowledge, there are no direct and unambiguous demonstrations of "textbook" electronic doping modulation in halide perovskites, which would have well-defined effects on material properties such as conductivity, work function, photoluminescence (PL), and device properties. [1,2] As anticipated by early ion migration models, the difficulty arises from ionic defects in halide perovskites (labile protons, halide vacancies, interstitials, etc.…”
Section: Introductionmentioning
confidence: 99%
“…[5,6] Despite the challenge introduced by mobile ions, many strategies have been applied in an attempt to dope perovskites including substitution of lattice ions, [7][8][9][10][11][12][13][14][15] chemical reactions with vapors, [16][17][18] treatment with molecular oxidizers and reducers, [19][20][21][22][23][24] and electrochemical techniques. [25][26][27][28] However, to the best of our knowledge, there are no direct and unambiguous demonstrations of "textbook" electronic doping modulation in halide perovskites, which would have well-defined effects on material properties such as conductivity, work function, photoluminescence (PL), and device properties. [1,2] As anticipated by early ion migration models, the difficulty arises from ionic defects in halide perovskites (labile protons, halide vacancies, interstitials, etc.…”
Section: Introductionmentioning
confidence: 99%
“…For example, p-type doping could in principle be achieved through the introduction of Bi 3+ as reported by Abdelhady et al 4 However, preservation of charge neutrality entails that its incorporation be accompanied by three monovalent counteranions, which is highly disfavored during crystallization as this is incompatible with the crystal lattice. Thus, current doping strategies for MHPs, apart from the intentional formation of defects to provide extra electrons or holes to the lattice, 5 are concentrated on substitutional doping using electrochemical methods 6 or on the use of molecular dopants. The latter strategy was nicely demonstrated through the use of tetrafluorotetracyanoquinodimethane (F4TCNQ) to enhance the electrical conductivity of MASn 0.5 Pb 0.5 I 3 by over 4 orders of magnitude (MA = methylammonium).…”
Section: Introductionmentioning
confidence: 99%
“…CsPbBr 3 is weakly p type when grown in halide-rich conditions, , but the carrier densities are low because the Fermi level is still hundreds of meV above the valence-band maximum (VBM). Electrochemical doping has shown that moderate electron or hole densities can be achieved in thin films of nanocrystals, , but an effective and reliable acceptor dopant is still needed.…”
Section: Introductionmentioning
confidence: 99%